Evaluating museum websites using a combination of decision-making theories. Issue 5 (2nd November 2019) - Kabassi, Katerina
ABSTRACT: The role of museums is very important in cultural and heritage tourism, and a museum website plays an important role in attracting visitors, both physically and online. Therefore, these websites must be evaluated to ensure that their goals are met. However, the evaluation of a website is complex and is often omitted during the website's life cycle, despite its importance. To simplify this process, this paper presents a framework for evaluating museum websites. The framework, based on an inspection method, is called the inspection evaluation method (IEM). This method uses criteria proposed by several researchers in a review of the different evaluation experiments for museum websites that have previously used an inspection method. IEM, different from all other methods reviewed, uses a combination of an analytic hierarchy process with a technique for the order of preference by similarity to an ideal solution for combining these criteria. The framework was applied to evaluate and rank the websites of five museums known worldwide. This combination uses the advantages of two multi-criteria decision-making theories and reduces their disadvantages.